Dampak Pembinaan Muallaf Terhadap Ibadah di Muallaf Center Indonesia Kota Palangka Raya - Hafidzatul Muslimah; Zainap Hartati (Departement of Mathematics Education, 2024)
Converts are people who need the teachings of Islam. The Indinesian Mualaf Center (MCI) which is intensifying the guidance for converts to Islam in Palangka Raya. Coaching is a structured activity carried out by a person or institution to help certain groups to strengthen the weak and maintain the strong in certain cases to gain knowledge about certain objects. Coaching at MCI Palangka Raya is one form of effort to replenish the faith of converts which sometimes go up and down. The purpose of this study, 1) to identify the impact of coaching on converts to worship at the Indonesian Mualaf Center in Palangka Raya. 2) to analyze the obstacles and solutions for the development of converts worship at the Indonesian Mualaf Center in Palangka Raya. The results of this study describe that: 1) The impact of coaching converts to worship at MCI Palangka Raya is that converts worship has increased with increasing knowledge about worship and the right practice of worship. Converts are also more enthusiastic in participating in coaching because they feel that by following coaching converts will get more knowledge so that worship will also increase. When converts do not follow the guidance, their knowledge of worship that should be carried out by Muslims will decrease. 2) The obstacle in implementing the coaching process at MCI Palangka Raya is the coaching schedule which sometimes clashes between the instructors and converts. The solution to these obstacles is to give understanding to converts that if they follow the coaching, they will get extraordinary learning and experience. Thus, they adjust the schedule between the instructors and converts.